Emerging Web Technologies in Higher Education: A Case of Incorporating Blogs, Podcasts and Social Bookmarks in a Web Programming Course based on Students' Learning Styles and Technology Preferences - Saeed, Nauman; Yang, Yun; Sinnappan, Suku (Educational technology & society, 2009)
The adoption level of emerging web technologies is on the rise in academic settings. However, a major obstacle in the practice of web-based instruction is the limited understanding of learners' characteristics and perceptions about technology use. Thus there is a need to understand the relationship between students' learning styles and their preferences for instructional strategies, including the use of emerging web technologies. Since learning styles provide information about individual differences in learning preferences they can suggest how instruction can be best designed to support the learning preferences. In this paper, a research framework has been proposed to incorporate emerging web technologies into higher education based on students' learning styles and technology preferences and a case study has been carried out to validate the proposed framework. An action research methodology has been adopted to carry out the study, which comprises of conducting a survey about students' learning styles and technology preferences; incorporating a combination of emerging web technologies based on the survey findings; and analyzing key achievements and shortcomings of the study to redefine research objectives. The study provides support for the proposed framework by highlighting the significant relationships among students' learning styles and technology preferences and their impact on academic performance.